Lives saved by laws and regulations that resulted from the Bloomberg road safety program - Miller, Ted; Levy, D.; Swedler, D. (Elsevier Ltd, 2018)
© 2018 Elsevier Ltd Objective: To estimate lives saved during 2008–2023 by traffic safety laws passed in six developing countries while participating in the Bloomberg Road Safety Program (BRSP). Methods: BRSP-funded local staff identified relevant laws and described enforcement to the study team. We analyzed road crash death estimates for 2004–2013 from the Global Burden of Disease and projected estimates absent intervention forward to 2023. We amalgamated developing country and US literature to estimate crash death reductions by country resulting from laws governing drink driving, motorcycle helmets, safety belt use, and traffic fines. Results: BRSP helped win approval of traffic safety laws in Brazil, China, Kenya, Mexico, Turkey, and Vietnam. In 2008–2013, those laws saved an estimated 19,000 lives. Many laws only took effect in 2014. The laws will save an estimated 90,000 lives in 2014–2023. Of the 109,000 lives saved, drink driving laws will account for 84%, increased motorcyclist protection for 13%, increased fines and penalty points for 2%, and safety belt usage mandates for 1%. Drink driving reductions in China will account for 56% of the savings and reduced drink driving and motorcycling deaths in Vietnam for 35%. The savings in China will result from a narrow intervention with just 4% estimated effectiveness against drink driving deaths. As a percentage of deaths anticipated without BRSP effort, the largest reductions will be 11% in Vietnam and 5% in Kenya. Conclusions: Viewed as a public health measure, improving traffic safety provided large health gains in developing nations.